Baseline low-density lipoprotein cholesterol predicts the benefit of adding ezetimibe on statin in statin-naïve acute coronary syndrome - Jihaeng Im (Scientific Reports, 2021)
Abstract We aimed to evaluate the effect of baseline low-density lipoprotein cholesterol (LDL-C) on the outcomes of patients with the acute coronary syndrome (ACS) receiving pitavastatin monotherapy or the combination of pitavastatin + ezetimibe. In the HIJ-PROPER study, 1734 ACS patients with dyslipidemia were randomly assigned to receive pitavastatin or pitavastatin + ezetimibe therapy. Statin-naïve participants (n = 1429) were divided into two groups based on the median LDL-C level (131 mg/dL) at enrollment. The primary endpoint was a composite of all-cause death, non-fatal myocardial infarction, non-fatal stroke, unstable angina, and ischemia-driven coronary revascularization. The median follow-up was 3.2 years. In the < 131 mg/dL group (n = 686), LDL-C changes were − 34.0% and − 49.8% in the pitavastatin monotherapy and pitavastatin + ezetimibe-treated groups (P < 0.0001), respectively; in the ≥ 131 mg/dL group (n = 743), LDL-C changes were − 42.9% and − 56.4% (P < 0.0001, respectively. Kaplan–Meier analyses revealed that the primary endpoint was not significantly different between the treatment groups for the < 131 mg/dL group, however, it was significantly lower in patients treated with pitavastatin + ezetimibe in the ≥ 131 mg/dL group (Hazard ratio = 0.72, 95% confidence interval = 0.56–0.91, P = 0.007, P value for interaction = 0.012). Statin-naïve ACS patients with baseline LDL-C < 131 mg/dL did not clinically benefit from pitavastatin + ezetimibe, while patients with baseline LDL-C ≥ 131 mg/dL treated with pitavastatin + ezetimibe showed better clinical results than those treated with pitavastatin monotherapy. Clinical Trial Registration: Original HIJ PROPER study; URL: http://www.umin.ac.jp/ctr . Unique Identifier; UMIN000002742, registered as an International Standard Randomized Controlled Trial.